Multipurpose portable table / Azidora Azman...[et al.] - Azman, Azidora; Ahmad Zaidi, Ahmad Zuhair; Ramlan, Nurshaffin Aida; Abdul Gani, Arina; Muhamad Kamil, Nur Afiqah (2019)
In this report, the objective is to prepare a successful business plan by taking into considerations from all aspect. Le Pratique Company Sdn. Bhd. is a new developed company that release a new product called "Multipurpose Portable Table". Initially, the basic idea of this product is to provide a pocket file that fit various things such as laptop, stationary and files or books. Eventually, new idea arises with the demand of daily activities specifically who works in the state of mobilization. These people or consumers spent countless of hours in the coffee shops in search of space, atmosphere and also a table which are different from the likes of their home. Thus, the idea to develop this product is improved by allocate a mini table legs on it. The product innovation focuses to provide a simple and easy-to-carry mini table as well as providing an organized space for stuff. The design for this product is explain in details in Section 2.0 “Multipurpose Portable Table" is a consumer based product where it can be used by everyone. The target market for this project is mainly in Shah Alam, Selangor since the population in this area is high. Demand for a mini table nowadays is increased greatly that impact the competition between suppliers. Comparison is done with another two different types of product in order to improve the product that will be produce by this company. A review on the start-up cost and working capital cost are listed in Section 6.0. Since this company is owned by 5 entrepreneurs; the sources of capital will be shared among the owners. There is no fund or loan taken from the bank or other outside sources. This project is estimated to produce 1000 units of product within 3 months after 2 months of start-up the business. The project milestones are described is Section 7.0.